2022
DOI: 10.3390/sym14081558
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and Asymmetry of the Antegonial Notch

Abstract: The symmetry of a human organism’s structure is an expression of the general law of development regarding organic life. Assessing the symmetry of the face and its individual components is one of the most important factors when it comes to the overall assessment of a patient’s stomatognathic system and is essential in the planning of orthodontic and prosthetic treatment. The aim of this study is to assess the symmetry of the occurrence and the measurement parameters of the pre-angular notch of the mandible. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Even though the obtained results give a consistent image of age-related changes, they must be treated with caution, due to the main limitations of our studycross-sectional character and limited sample sizes (see "Limitations" section). A potential confounding factor of random environmental effects, which may manifest itself as fluctuating asymmetry 46 , has been considered here. However, the performed analysis of two FA indicators showed that this variable was negligible in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the obtained results give a consistent image of age-related changes, they must be treated with caution, due to the main limitations of our studycross-sectional character and limited sample sizes (see "Limitations" section). A potential confounding factor of random environmental effects, which may manifest itself as fluctuating asymmetry 46 , has been considered here. However, the performed analysis of two FA indicators showed that this variable was negligible in our sample.…”
Section: Discussionmentioning
confidence: 99%